Green and sustainable biosynthesis of hybrid iron/palladium nanoparticles functionalized PES membranes for dye removal - Qusay A. Almajras; Ahmed K. Hassan; Raed A. Al-Juboori; Qusay F. Alsalhy (Desalination and Water Treatment)
Green bimetallic iron (Fe)/palladium (Pd) nanoparticles were synthesized employing extract from Moringa leave as capping and reducing, agent and used as additives for the polyether sulfone (PES) membrane modification. Synthesis of both nanoparticles using plant sources makes this approach eco-friendly and sustainable. Such hybrid nanoparticles could be employed to remove harmful synthetic dyes from water. In this study, hybrid Fe/Pd nanoparticles were applied to investigate their catalytic synergistic effect for removing Congo Red (CR), and Naphthol Blue Black (NBB) dyes. The produced nanocomposite membrane was proposed as a potential removal technique for dyes. The CR and NBB dyes were employed as representatives for dye contamination. The addition of Fe/Pd nanoparticles was optimized concerning their weight loading in the PES solution. The structural and chemical characteristics of the synthesized membrane as well as their dyes’ removal efficiency were (13.6 % NBB and 9.5 % CR) improved. The optimum Fe/Pd loading was found to be 0.5 g (membrane denoted as M 0.5) resulting in the highest solute fluxes of 80 and 84 L/m2.h with 100 mg/L concentration of NBB and CR, respectively as compared to 51 and 52 L/m2.h of the respective fluxes with pristine PES membrane (denoted as M 0.0). The rejection improved from 86 % to 98.4 % for NBB and 88.5–97.4 % for CR when M 0.0 was replaced with M 0.5. The integration of Fe/Pd NPs has also enhanced the membrane's antifouling characteristics as the increase in membrane surface smoothness and hydrophilicity stand behind the development of reversible fouling. The functional groups introduced by the Moringa leaf extract are believed to have a promising role in polymeric membrane modification for improving dye separation.